Identification of Tampering in Arabic Text Documents Using Zero-Watermarking Algorithm - Mohammed Abdulmaged, Shahbaa (Newinera Publisher, 2024)
The internet makes sharing information easy, but protecting copyrights and verifying the authentication of online text remains a challenge. Current methods for securing Arabic text are limited. This research introduces a new tool: a zero watermark algorithm designed specifically for Arabic text. This new algorithm protects Arabic text by analyzing its content. It creates a watermark based on a chosen keyword (at least 6 characters, no duplicates), and how often each character appears in different forms (separate, connected), and positions (beginning, middle, and end) within the text. The proposed method was tested on nine different Arabic text samples of varying size, simulating various tampering attempts like inserting, deleting, and rephrasing text. The results are impressive, showing that the algorithm outperforms existing methods in detecting even minor changes.